A graphical method for the analysis of the aeroelastic crosswind vibrations of a square cylinder. Issue 235 (April 2023) - Liu, Y.Z.; Ma, C.M.; Dai, K.S.; Camara, A.; Ding, Z.B.; Luo, Y.X.; Chang, Y.
Abstract: This paper proposes a simple and fast method to obtain the aeroelastic response of a square cylinder following different modelling approaches underpinned by a novel graphical technique that establishes abstract relationships between different key physical parameters involved in the mathematical models. The method is applied to the analysis of three important aeroelastic problems in the crosswind response of a square cylinder, including the transverse galloping defined with a quasi-steady model, the vortex-induced vibration (VIV) using a nonlinear oscillator model, and the VIV-galloping interaction following a combined effects model. The results demonstrate that the proposed analytical method simplifies the analysis and it is able to capture most of the complex aeroelastic crosswind behaviors of a square bluff body. Highlights: A graphical method to obtain the aeroelastic response of a square cylinder following different modelling approaches is proposed. Compared with conventional analytical methods, the new analytical method has advantages of simplicity and effectiveness. The graphical analytical method is successfully applied to the study of transverse galloping, VIV and their potential interaction.